Diabetes como factor de riesgo en el desarrollo de isquemia distal en el área de emergencia - Velecela Romero, Jonnathan Vicente (2025)
Background: Worldwide, the growing epidemic of diabetes mellitus suggests the need for strategies to detect complications early. Peripheral arterial disease is one of them, which can have devastating consequences for the patient, the family and society. The objective of the research was to determine the impact of diabetes as a risk factor in the development of distal ischemia in the emergency area. Methods: The article had a qualitative research approach as it was based on a search of articles published in indexed journals in the last five years of preference. In addition, it was carried out with methods of analysis and discernment of information, using the PRISMA tool. Among the main results, it was identified that diabetes mellitus as a disease in the vascular field, establishes a sequence of biochemical phenomena that result in the alteration of the endothelium as an organ, vascular smooth muscle dysfunction, alterations of the figural elements and coagulation, deficient Lipid metabolism that finally manifest as micro and macro vascular diseases, resulting in distal ischemia. Conclusions: Diabetes mellitus represented a significant risk factor for the development of distal ischemia, the implementation of early diagnostic methods, such as the ankle - arm index, together with other non - invasive tools, which is fundamental for early detection in diabetic patients.